2010
DOI: 10.1111/j.1095-8312.2010.01493.x
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on home range behaviour affect nutritional condition in urban house sparrows (Passer domesticus)

Abstract: In human-dominated landscapes (semi)natural habitats are typically embedded in tracts of unsuitable habitat. Under such conditions, habitat characteristics and grain size of the surrounding landscape may affect how much food, and at what cost, is available for sedentary species with low home-range plasticity. Here we combine behavioural radio-tracking, feather ptilochronology, and landscape analysis to test how nutritional condition varies with home range size in 13 house sparrow [Passer domesticus (Linnaeus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 66 publications
1
60
2
Order By: Relevance
“…As most House Sparrows settle to breed within 1 km of their birth sites (Cheke 1972, Heij & Moeliker 1990, Anderson 2006) averaging only 0.21 km in Britain (Paradis et al 1998), and genetic mixing is particularly limited in suburban habitats (Vangestel et al 2010(Vangestel et al , 2011, natal dispersal between our study colonies was probably also minimal. Breeding dispersal in House Sparrows is even less pronounced than natal dispersal, averaging 0.15 km in Britain (Paradis et al 1998) and rarely exceeding 1-2 km (Summers-Smith 1988).…”
Section: Discussionmentioning
confidence: 85%
“…As most House Sparrows settle to breed within 1 km of their birth sites (Cheke 1972, Heij & Moeliker 1990, Anderson 2006) averaging only 0.21 km in Britain (Paradis et al 1998), and genetic mixing is particularly limited in suburban habitats (Vangestel et al 2010(Vangestel et al , 2011, natal dispersal between our study colonies was probably also minimal. Breeding dispersal in House Sparrows is even less pronounced than natal dispersal, averaging 0.15 km in Britain (Paradis et al 1998) and rarely exceeding 1-2 km (Summers-Smith 1988).…”
Section: Discussionmentioning
confidence: 85%
“…This is partially consistent with literature data. For example, a decreased condition of the House Sparrows occupying urban and suburban territories was confirmed by ptilochronological data from Ghent, Belgium, compared to birds from rural areas (Vangestel et al 2010). Also Liker et al (2008) released data, obtained out of the breeding season and in a urbanization gradient, from the city center to rural areas in Hungary, that confirm the increase of adult bird condition, body mass and tarsus length but with no significant differences between sexes.…”
Section: Body Condition Of Birdsmentioning
confidence: 83%
“…Liker et al (2008) suggest completing the credit card hypothesis by recognizing the influence of environmental impact on the development of hatchlings or even acknowledging it as a new alternative when explaining the weaker body condition of urban birds. Numerous studies confirm the lack of food typically found in the House sparrow's diet as a result of decreasing vegetation areas throughout cities accompanied by a plant management (Robinson et al 2005;Anderson 2006), habitat fragmentation (Vangestel et al 2010) and an increasing share of alien plant species (Marzluff 2001;Donnelly and Marzluff 2006). In addition, increasing levels of environmental pollutants, e.g.…”
Section: Body Condition Of Birdsmentioning
confidence: 91%
See 1 more Smart Citation
“…With decreased body condition, individuals would likely be in a negative energy balance and therefore be less likely to be able to maintain a larger home range size. Indeed body condition correlates positively with dispersal distance in Roe deer (Capreolus capreolus) (Debeffe et al, 2012), migratory distance in spawning herring (Clupea pallasii) (Slotte, 1999), and home range size in urban house sparrows (Passer domesticus) (Vangestel et al 2008). The negative effect of T and body condition could explain the lack of correlation of home range and cortical brain volume ranges.…”
Section: Spatial Ecology and Neuroplasticitymentioning
confidence: 99%